Disinfection of water using vortex diode as hydrodynamic cavitation reactor - Gaikwad, V.; Ranade, V. (Asian Journal of Chemistry, 2016)
Hydrodynamic cavitation offers distinct advantages for water disinfection and wastewater treatment particularly at large scales of operations. Vortex Diode is a fluidic device, which is conventionally used as a leaky non-return valve in nuclear industry. Recently this device was shown to be effective hydrodynamic cavitation device. In the present study, we have investigated use of cavitation in vortex diode for water disinfection application. Escherichia coli contaminated water is treated successfully using vortex diode. The operating parameters desirable for the disinfection are investigated. The performance is evaluated based on the reduction in the colony forming unit (CFU/mL) of E. coli count estimated by standard spread plate method. The presented results will be useful for identifying appropriate operating conditions for using vortex diode to effectively reduce the bacterial load and disinfect water.

Effect of orifice shape on water disinfection efficacy - Gaikwad, V.; Gaikwad, S.; Ranade, V. (Pollution Research, 2016)
Hydrodynamic cavitation offers distinct advantages for water disinfection and waste watei treatment particularly at large scales of operations. For applying hydrodynamic cavitation foi water disinfection/treatment, water stream to be treated is passed through a fluidic device ir which there exists a low pressure region. Cavities are generated in this region when the pressurt falls below vapour pressure (in absence of any dissolved gases). These cavities are then collapsec when they travel to regions of higher pressure and lead to very high shear, temperatures anc pressures in localized regions. These high pressure/temperature as well as high shear facilitati disinfection as well as reduction in chemical oxygen demand, colour and amonical nitrogen in the water. In this work, we have investigated hydrodynamic cavitation generated by five difieren orifices have been studied which have different shapes with same fractional open area and have tested their effectiveness for water disinfection. The efficacy of generated cavitation on wate disinfection was quantified based on measurements of non-pathogenic E. coli colony forminj units (CFU/mL). The presented results and analysis will be useful for designing hydrodynamii cavitation based systems for water disinfection